„We’re not playing against each other. We play together in pursuit of the same goal (…)” - Apprenticeship and works councils in SME in Germany - Berger, Klaus [Verfasser]; Eberhardt, Christiane [Verfasser] (My University, 2020)
"805,800 persons were recoded as being interested in entering training in Germany in 2017. Of these, just under 65 percent progressed to vocational education and training (VET) within the dual system. A total of two thirds of those in employment in Germany have completed dual VET (Federal Institute for Vocational Education and Training 2018). The fact that more than half of school leavers opt for vocational education and training as part of their educational pathway (Federal Institute for Vocational Education and Training 2015) is also a consequence of the high (average) quality of training and of the resultant good prospects of employment. Soskice (1994) argues that one of the important prerequisites for the high level of training quality is the cooperation that takes place between the competent bodies (mostly chambers of crafts, chambers of commerce and industry) on the one side and the works councils and trade unions on the other. This context is widely taken as a given within the relevant literature, especially in the case of the works councils, which are accorded extensive information and participation rights for the purpose of securing quality of training at the company within the scope of the German Labour Management Relations Act (§§ 96–98 Labour Management Relations Act / Betriebsverfassungsgesetz, BetrVG). However, what are the determining factors for a high quality of apprenticeship training? The focuses of this paper are the issue of the understanding of apprenticeship training quality developed by works councils at small and medium-sized enterprises (SMEs) and the way they contribute at company level with regard to apprenticeship training matters." (Authors' abstract, BIBB-Doku)
Nie gramy przeciwko sobie, tylko dążymy do tego samego celu (…) – praktyki zawodowe i rady pracowników w MŚP w Niemczech
Keywords: S 1.3 Berufliche Erstausbildung; L 6 Qualität; S 3.2.1 KMU, Klein- und Mittlere Unternehmen; 370; Betriebliche Berufsausbildung; Ausbildungsqualität; Klein- und Mittelbetrieb; Betriebsrat